The Impact of Genes and Environment on Brain Ageing in Males Aged 51 to 72 Years - Gillespie, Nathan A.; Hatton, Sean N.; Hagler, Donald J.; Dale, Anders M.; Elman, Jeremy A.; McEvoy, Linda K.; Eyler, Lisa T.; Fennema-Notestine, Christine; Logue, Mark W.; McKenzie, Ruth E.; Puckett, Olivia K.; Tu, Xin M.; et al. (Frontiers in Aging Neuroscience, 2022)
Magnetic resonance imaging data are being used in statistical models to predicted brain ageing (PBA) and as biomarkers for neurodegenerative diseases such as Alzheimer’s Disease. Despite their increasing application, the genetic and environmental etiology of global PBA indices is unknown. Likewise, the degree to which genetic influences in PBA are longitudinally stable and how PBA changes over time are also unknown. We analyzed data from 734 men from the Vietnam Era Twin Study of Aging with repeated MRI assessments between the ages 51 to 72 years. Biometrical genetic analyses ‘twin models’ revealed significant and highly correlated estimates of additive genetic heritability ranging from 59% to 75%. Multivariate longitudinal modelling revealed that covariation between PBA at different timepoints could be explained by a single latent factor with 73% heritability. Our results suggest that genetic influences on PBA are detectable in midlife or earlier, are longitudinally very stable, and are largely explained by common genetic influences.